ISO 50001: 2018 and Its Application in a Comprehensive Management System with an Energy-Performance Focus (2019)
Business progress and human development are linked to the e cient management of energy resources. The research in this paper contributes to the generalized application of good practices that reduce the vulnerability of companies. The research focuses on energy e ciency through comprehensive management systems (CMS), and “thought based on risks and opportunities”, considering the discussion about the revision of ISO 50001:2018, the basic approach of the model and the route to implement CMS for quality, safety and health in the workplace, environmental management, energy e ciency, and other risk components. This implementation route, with the acronym CMS QHSE3+, places special emphasis on the functions of strategic planning, operational and risk management, and controls, as well as on deliverables and references to examples, templates, standards, and documents, to facilitate its application general in small and medium enterprises and in the management of energy e ciency.